Chapter Introduction A Global History of Execution and the Criminal Corpse - Ward, Richard (Palgrave Historical Studies in the Criminal Corpse and its Afterlife, 2015)
Through studies of beheaded Irish traitors, smugglers hung in chains on the English coast, suicides subjected to the surgeon's knife in Dresden and the burial of executed Nazi war criminals, this volume provides a fresh perspective on the history of capital punishment. This book has two open access chapters under a CC BY license.